FRI0598-HPR Patients with musculoskeletal complaints do less vigorous physical activity and have poorer physical fitness than population controls. (23rd January 2014) - Moseng, T.; Tveter, A. T.; Holm, I.; Dagfinrud, H.
Abstract : Background: Studies have shown that patients with chronic low back pain and osteoarthritis tend to be less physically active 1 or have lower level of physical fitness than healthy controls 2 ;3 . It is well established that low fitness levels are associated with development of lifestyle-related diseases, delayed recovery and increased consumption of health care services. It is therefore important to focus on physical activity and fitness levels in patients with different musculoskeletal complaints (MSCs) seeing physiotherapists in primary care. Objectives: Examine physical activity and physical fitness (cardiorespiratory endurance and muscular strength) in patients with different MSCs seeking physiotherapy in primary care and in population controls. Methods: In this cohort study, 167 patients with varying MSCs were recruited from five primary care physiotherapy clinics in Norway. In addition, 313 population controls were recruited. The participants reported on physical activity (measured as metabolic equivalents (METs)) by use of the International Physical Activity Questionnaire short form (IPAQ-sf). Their physical fitness was assessed using the Six Minute Walk Test (6MWT) and The Thirty Seconds Sit to Stand Test (30secSTS). Results: The patient group reported significantly less vigorous activity (median 0, range 0-4320 MET min/week) compared to the control group (median 240, range 0-10080 MET min/week) (p=.001), while no significant differences were observed for moderate activity (p=.731), walking (p =.655) or total activity (p=.292). Analyses adjusted for age, BMI and gender showed that patients had significantly lower cardiorespiratory endurance (difference 6MWT 68.7 meter (95% CI 52.4, 85.1)) (p=<.001) and poorer muscular strength (difference 30secSTS 6.5 repetitions (95% CI 5.4, 7.5)) (p=<.001) than controls. Conclusions: Patients with different musculoskeletal complaints seeing physiotherapists in primary care reported significantly less vigorous intensity physical activity and had significantly poorer physical fitness than population controls. References: Farr JN, Going SB, Lohman TG, Rankin L, Kasle S, Cornett M et al. Physical activity levels in patients with early knee osteoarthritis measured by accelerometry. Arthritis Rheum 2008; 59(9):1229-1236. Hodselmans AP, Dijkstra PU, Geertzen JH, van der Schans CP. Nonspecific chronic low back pain patients are deconditioned and have an increased body fat percentage. Int J Rehabil Res 2010; 33(3):268-270. Ryan CG, Grant PM, Dall PM, Gray H, Newton M, Granat MH. Individuals with chronic low back pain have a lower level, and an altered pattern, of physical activity compared with matched controls: an observational study. Aust J Physiother 2009; 55(1):53-58. Disclosure of Interest: None Declared